Detecting life on Mars and the life marker chip : antibody assays for detecting organic molecules in liquid extracts of Martian samples - Rix, Catherine S. (Cranfield University, 2012)
The Life Marker Chip instrument, which has been selected to fly as part of the 2018 ExoMars rover mission payload, aims to detect up to 25 organic molecules in martian rocks and regolith, as markers of extant life, extinct life, meteoritic in-fall and spacecraft contamination. Martian samples will be extracted with a solvent and the resulting liquid extracts will be analysed using multiplexed microarray-format immunoassays. The LMC is under development by an international consortium led by the University of Leicester and the work described within this thesis was carried out at Cranfield University as part of the consortium’s broader program of work preparing the LMC instrument for flight in 2018. Within this thesis four specific areas of LMC instrument development are addressed: the investigation of immunoassay compatible liquid extraction solvents, the study of likely interactions of martian sample matrix with immunoassays, the development of antibodies for the detection of markers of extinct life and demonstration of solvent extraction and immunoassay detection in a flight representative format. Cont/d.
Keywords: Astrobiology; ExoMars; extraction solvents; sample matrix effects; recombinant antibodies; phage display; microfluidics